2022
DOI: 10.3389/feart.2022.1018420
|View full text |Cite
|
Sign up to set email alerts
|

An optimized stochastic model for smartphone GNSS positioning

Abstract: With the increasing popularity of high-precision applications of smartphone, more and more scholars carry out studies in the field of smartphone GNSS positioning. In the previous studies, more attention has been paid to data quality control, data preprocessing and observation models. However, the research on stochastic models is rare. The stochastic model is significant for the subsequent optimal positioning parameter estimation, meanwhile, the stochastic models of smartphones and professional geodetic receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The C/N0, which gauges signal reception quality, has been shown to be more optimized for smartphone positioning than the elevation-dependent model [ 8 , 24 ]. Recognizing the limitations of C/N0 in smartphone positioning, recent advancements include the elevation-C/N0 model, which merges both indicators (elevation and C/N0) with robust estimation principles [ 25 ], and the optimized C/N0-dependent stochastic model, which aptly describes smartphone GNSS observation quality [ 29 ]. These models have, to a degree, ameliorated smartphone positioning.…”
Section: Introductionmentioning
confidence: 99%
“…The C/N0, which gauges signal reception quality, has been shown to be more optimized for smartphone positioning than the elevation-dependent model [ 8 , 24 ]. Recognizing the limitations of C/N0 in smartphone positioning, recent advancements include the elevation-C/N0 model, which merges both indicators (elevation and C/N0) with robust estimation principles [ 25 ], and the optimized C/N0-dependent stochastic model, which aptly describes smartphone GNSS observation quality [ 29 ]. These models have, to a degree, ameliorated smartphone positioning.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this groundbreaking smartphone has been extensively studied by scholars worldwide in the field of smartphone positioning. For instance, Sui Mingming et al [5] introduced an optimized random model tailored to the characteristics of smartphone observations. Through this approach, they successfully enhanced the positioning accuracy of smartphones, contributing to the growing body of research on leveraging the capabilities of dual-frequency GNSS smartphones like the Xiaomi Mi8 smartphone.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are mainly limited to the most common models used for comparing the C/ N0-dependent and elevation-dependent weighting schemes, not proposing any special approach for smartphone observations. Sui et al (2022) have proposed a stochastic model optimized for smartphone observations and showed that the positioning performance of SPP (single point positioning) and RTK methods can be improved between 10% and 40%, considering three-dimensional RMS errors. Zangenehnejad and Gao (2023) have presented the C/N0/elevation-based model for smartphone observations depending on the LS-VCE (least-square variance component estimation) method and showed an improvement of 25.1% in PPP solution, considering horizontal RMS errors.…”
Section: Introductionmentioning
confidence: 99%